The Macroeconomic Role of Fiscal Policy. - Allsopp, C; Vines, D (2005)
This article examines the new consensus that fiscal policy should have no macroeconomic role in "flexible inflation targeting" regimes. There is little basis for this presumption. Fiscal policy remains important in setting the policy mix and in managing shocks and imbalances. The credibility of an inflation-targeting regime should be enhanced rather than reduced if fiscal policy plays its proper role. It is true, nevertheless, that the costs of focusing fiscal policy narrowly on public-sector concerns may not be very great, most of the time. However, when interest rates cannot be used, the role of fiscal policy must be different. With interest rates at their lower bound of zero, there is no plausible alternative. For asymmetric shocks and adjustments in EMU, fiscal policy needs, ideally, to substitute for the interest-rate policy reaction function of the consensus, but the difficulties are very great. We suggest a policy focus on real exchange rates as a way of resolving some of the dilemmas. There is a serious danger that orthodox views about fiscal policy, drawn from the consensus, will be inappropriately applied, especially in Europe.